2001
DOI: 10.1191/096120301682430230
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in mortality from systemic lupus erythematosus in the United States

Abstract: The aim was to identify demographic and environmental factors that affect the incidence and course of systemic lupus erythematosus (SLE) by studying geographical variation in mortality from the disease. Counts of SLE deaths during a 10-y period were determined for each of the 3111 counties in the United States. The counts were subjected to statistical techniques for detecting spatial clusters with significantly higher or lower mortality than expected. Census data were used to compare attributes of the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 35 publications
1
38
0
1
Order By: Relevance
“…All but 2 of our patients were Hispanic, and 1 of the 2 was Native American. The outcome in lupus also varies by geographical region [32,33]. However, it is almost impossible to differentiate the relative role of each factor (ethnicity, geography) within these studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…All but 2 of our patients were Hispanic, and 1 of the 2 was Native American. The outcome in lupus also varies by geographical region [32,33]. However, it is almost impossible to differentiate the relative role of each factor (ethnicity, geography) within these studies.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is almost impossible to differentiate the relative role of each factor (ethnicity, geography) within these studies. Adult studies have indicated increased SLE mortality in areas with high concentrations of Hispanic patients, such as New Mexico [33]. However, some authors have attributed these findings to the poorer socioeconomic conditions and lack of health insurance among Hispanic populations, which may indicate a lack of adequate health care [33].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors appear to contribute to this trend, including genetic (ie, racial) and sociodemographic factors (ie, education, income, insurance status, smoking, treatment adherence, abnormal attitudes toward illness) and comorbidities (ie, hypertension). The mechanisms through which these factors may affect the clinical expression of SLE in these three US ethnic groups have received increased attention in recent publications [12][13][14][15].…”
Section: Ethnicity and Age Of Systemic Lupus Erythematosus Onsetmentioning
confidence: 99%
“…Epidemiological approaches have identified multiple associated environmental factors that are neither homogenously distributed in populations, nor corrected for in heritability estimates, such as socioeconomic status, urban/rural location [123][124][125][126], and dietary habits [127][128]. For some diseases, it is possible to estimate the contribution of such factors by comparing disease prevalence in monozygotic twins raised together with that of those raised separately.…”
Section: Familial Environmental Differencesmentioning
confidence: 99%